HERITABILITY, GENOTYPIC AND PHENOTYPIC CORRELATION BETWEEN QUANTITATIVE TRAIT OF LOCAL RICE ON DIFFERENT FERTILIZER - Utami, Desti Margi; Purnamaningsih, Sri Lestari; Soetopo, Lita (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2016)
Six local rice genotypes was tested in two different application of fertilizer (organic and an-organic fertilizer). The objective of this research is to study heritability and genotypic phenotypic correlation between quantitative traits of local rice in organic and an-organic fertilizer environment. This research was conducted from November 2008 until May 2009 (rainy season) in irrigation rice field Sumbersari, Malang City. Field design in each environment of fertilizer used randomized block design with three replication and seven trials. The results showed that high heritability in organic and an-organic environment were obtained for all characters which observed except for number of empty grain per panicle had medium heritability. In organic and an-organic environment all characters evaluated had narrow genetic variability. 50% days of flowering in organic and an-organic had genotypic and phenotypic correlation significantly positive with days to harvest, plant high, panicle length, number of filled grain per panicle, number of empty grain per panicle, number of filled grain per clump and yield.Key words : Heritability, Genotypic Phenotypic Correlation, local rice, organic and anÂorganic fertilizer